2020
DOI: 10.3390/ijerph17093233
|View full text |Cite
|
Sign up to set email alerts
|

Preferences in Information Processing, Marginalized Identity, and Non-Monogamy: Understanding Factors in Suicide-Related Behavior among Members of the Alternative Sexuality Community

Abstract: Suicide-related behavior (SRB) is a mental health disparity experienced by the alternative sexuality community. We assessed mental health, relationship orientation, marginalized identities (i.e., sexual orientation minority, gender minority, racial minority, ethnic minority, and lower education), and preferences in information processing (PIP) as factors differentiating lifetime SRB groups. An online cross-sectional survey study was conducted in 2018. Members of the National Coalition for Sexual Freedom (NCSF;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 74 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…The respondents with no formal education/ illiterate had AOR 3.83;95% CI (2.44–6.02) more likely to develop suicidal behavior as compared to those with primary education, which was supported by the study conducted in the United States [ 32 ] and meta-analysis done in five low and middle income countries (India, South Africa, Nepal, Uganda, and Ethiopia) [ 33 ].…”
Section: Discussionmentioning
confidence: 77%
“…The respondents with no formal education/ illiterate had AOR 3.83;95% CI (2.44–6.02) more likely to develop suicidal behavior as compared to those with primary education, which was supported by the study conducted in the United States [ 32 ] and meta-analysis done in five low and middle income countries (India, South Africa, Nepal, Uganda, and Ethiopia) [ 33 ].…”
Section: Discussionmentioning
confidence: 77%
“…In doing so, we have begun to integrate aspects of ideation-to-action frameworks (e.g., thwarted belonging and perceived burdensomeness). Specifically, NFA avoidance and approach, and to a lesser extent NFC, have been evaluated for two basic PIP premises: (1) PIP may be directly associated with suicide-related outcomes (e.g., ideation, behavior), and (2) PIP may amplify or dampen effects of other known suicide risk factors, namely depression and anxiety (Bryson et al, 2019;Cramer et al, 2016;Cramer, Franks, et al, 2020;Cramer, Langhinrichsen-Rohling, et al, 2020;Cramer, Mandracchia, et al, 2017). Exploring these PIP propositions has two goals.…”
Section: Preferences In Information Processing and Suicide: Evidence ...mentioning
confidence: 99%
“…In order to further refine what is known about PIP and suicide, we pooled data from community cross-sectional studies (Cramer et al, 2016;Cramer, Langhinrichsen-Rohling, et al, 2020;Cramer, Mandracchia, et al, 2017;Cramer, Rasmussen et al, 2019). All prior study methodologies and procedures were approved by University ethics/human subjects review boards and conducted in accordance with the ethical standards as laid down in the 1964 Declaration of Helsinki and its later amendments.…”
Section: Aggregating Pip Associations With Lifetime Suicidal Behavior...mentioning
confidence: 99%
“…Similar to personality traits, it is regarded as a relatively stable intrinsic character of human nature (1,2). NFA could help to explain individuals' differences in many critical mental aspects such as mental health (3)(4)(5)(6)(7)(8)(9), information preferences and decision making (10)(11)(12)(13)(14), social attitude [e.g., evaluation of self and others (15)(16)(17)(18), attitudes toward brands (19), attitudes toward job (20), attitudes toward the country (21), drugs (22)] and so on. It has also been found that NFA influences individual reactions to media and entertainment (23,24), political beliefs and ideology (16,25), legal decisions (26) and risk taking capacity (27).…”
Section: Introductionmentioning
confidence: 99%